2016
DOI: 10.1007/s12034-016-1158-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reactor for organic compound removal using photocatalytic mechanism

Abstract: In this work, a photocatalytic reactor with a working volume of 13 l was fabricated of soda-lime silica glass. Commercial titanium dioxide (TiO 2) particles were used as the photocatalyst and trails were conducted on the photodecomposition of methylene blue (MB) solutions (10 −5 M). The activation of the photocatalysts was carried out using 5 UV lamps (378 nm, 36 W), and 13 g of TiO 2 was added each week to the reactor. The MB solution was fed at a flow rate of 0.87 l h −1 , while the effluent was removed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Although the MB removal efficiency in this study was not great as other previous works [14,21,22], which shown >90% of photodegradation efficiency. The different operating factors are significant reasons such as light intensity, light wavelength, TiO2 loading, MB concentration, pH, dissolved oxygen and system design [13,23].…”
Section: Resultscontrasting
confidence: 86%
“…Although the MB removal efficiency in this study was not great as other previous works [14,21,22], which shown >90% of photodegradation efficiency. The different operating factors are significant reasons such as light intensity, light wavelength, TiO2 loading, MB concentration, pH, dissolved oxygen and system design [13,23].…”
Section: Resultscontrasting
confidence: 86%
“…TiO 2 in various nanostructures has been reported to have suitable properties for the ionization and desorption of analytes as a solid matrix for LDI-MS. The photocatalytic activity of the TiO 2 aerogels was estimated using methylene blue as the model analyte, as shown in Figure a. , The photodecomposition of methylene blue occurs when UV irradiates on TiO 2 which induces charge excitation and separation. As a result, hydroxyl radicals are formed on the TiO 2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic activity of the TiO 2 aerogels was estimated using methylene blue as the model analyte, as shown in Figure 2a. 36,37 The photodecomposition of methylene blue occurs when UV irradiates on TiO 2 which induces charge excitation and separation. As a result, hydroxyl radicals are formed on the TiO 2 surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The 1% TiO 2 nanoparticle (82.49%) and 5% TiO 2 nanoparticle (74.35%)—impregnated wood had a higher photocatalytic activity than the untreated. The end result of the photocatalytic reaction is carbon dioxide gas which can be released into nature and can be utilized by plants for the photosynthesis process [ 50 ].…”
Section: Resultsmentioning
confidence: 99%